Biological activity of fractions from the marine sponge Iotrochota birotulata IN mammalian cell lines (2016)
ABSTRACT: Marine sponges are considered an important source of substances with pharmacological potential. They play a key role in the intensive investigation of promising new compounds to treat cancer and other diseases. Objective: To evaluate in CHOK1 and Jurkat cell lines, the cytotoxic, genotoxic and antiproliferative effects of two fractions of I. birotulata sponge from Colombian Caribbean. Methods: The cell viability (cytotoxic effect) was determined by Trypan blue exclusion and MTT assays. Genotoxicity was assessed by single cell gel electrophoresis, the antiproliferative effect was monitored with clonogenic test, sister chromatid exchange proliferative kinetic, and accumulation function. Data was analyzed with lineal regression, oneway ANOVA, and Bonferroni tests. Results: Both cytotoxic assays showed a similar dose dependent effect for the CHOK1 and Jurkat cell lines treated with both fractions (F5 y F6) of I. birotulata. They also revealed an effect on the cell membrane and mitochondrial activity of both cell lines. Fraction F5 exhibited a greater genotoxic effect on both cell lines, which is consistent with the antiproliferation results obtained by the clonogenic assay. These results are also consistent with the inhibitory effect on the cell cycle, which was evaluated with SCE, proliferative kinetic, and the accumulation function tests. Consequently, the results showed differential sensitivity to the treatment of the Jurkat cells compared to the CHOK1 cell line. Conclusions: Together, the results show a differential effect of the two assessed fractions on cell membrane integrity, mitochondrial activity, and antiproliferative effect on both mammalian cell lines.